What makes a law “Islamic”? A preliminary study on the Islamicity of laws in Malaysia - Wan Muhammad, Ramizah (International Islamic University Malaysia., 2019)
There exists a good deal of misunderstanding regarding laws in general. Some laws are categorised as civil or common laws even though their contents are Islamic while others are labelled Islamic but they fail to meet the standards required by Islamic law. This article discusses the characteristics, which make a law, “Islamic”. Based on a content analysis of the revealed sources, the opinion of the majority of Muslim scholars, and the relevant court cases, this study argues that a law does not become Islamic by merely claiming it to have been derived from or somehow related to the divine revelation. It is true that for any law to be Islamic, it must indeed be based upon the divine revelation, and supported by Muslim jurists. Nevertheless, it must also simultaneously be promoting justice for everyone, irrespective of race, religion, gender, social, economic or political status. The law must also be of benefit to all mankind and not only to the Muslims. Finally, the law must fulfil the requirements of MaqāÎid al-sharÊ‘ah (objectives of the law). Judged as such, most of the Malaysian laws may be considered to be Islamic, by nature. These aspects have not been given due attention by many scholars, which leads either to the condemnation of all laws in Malaysia as secular or as un-Islamic. This fact alone justifies the need for a study to provide guidelines to judge the Islamicity of a certain law, which is done herein.